Operating system forensics - Messier, Ric; Mackay, Kevin (Waltham, MA : Elsevier, Syngress is an imprint of Elsevier, 2016)
"Covers digital forensic investigations of the three major operating systems, including Windows, Linux, and Mac OS. Presents the technical details of each operating system, allowing users to find artifacts that might be missed using automated tools. Hands-on exercises drive home key concepts covered in the book. Includes discussions of cloud, Internet, and major mobile operating systems such as Android and iOS."--Publisher web site.
Forensics and operating systems -- File systems -- Data and file recovery -- Memory forensics -- System configuration -- Web browsing -- Tracking artifacts -- Log files -- Executable programs -- Malware -- Mobile operating systems -- Newer technologies -- Reporting.
NEWBOOKS 2021.
Includes bibliographical references and index.
Keywords: Computer crimes -- Investigation; Operating systems (Computers) -- Security measures; Computer security; Computer crimes -- Investigation; Computer security; Operating systems (Computers) -- Security measures